Pengembangan Media Kartu Domino Materi Persamaan dan Pertidaksamaan Linear Satu Variabel (PLSV) Kelas VII SMP - Nurhidayati, Dwi; Khabibah, Siti; Sa’adah, Nihayatus (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2022)
One of the goals of using learning media is to improve the quality of student learning and make the learning process more interesting. Domino card learning media is one of the game innovations that can be used in the classroom. This study aims to describe the level of feasibility of domino card learning media on the material of Linear Equations and Inequality One Variables by adapting the ADDIE development model. The data collection technique used is a questionnaire. Questionnaires are divided into two types, namely validation questionnaires and student response questionnaires. The validation stage of learning media products is carried out by material experts, media experts, and learning practitioners. While the student response questionnaire with small group test subjects by three students and field trials by all students of class VII B. The validation results from material experts obtained an average score of 3.17 with a percentage of 63.3% and the criteria "Good" . Learning media experts obtained an average score of 4.45 with a percentage of 89.1% and the criteria "Very Good". Learning practitioners obtained an average score of 4.17 with a percentage of 83.3% and the criteria "Very Good". The response of students in the small group trial which obtained a score of 4.83 with a percentage of 96% and the criteria "Very Good". The response of students in the field trial which obtained a value of 4.45 with a percentage of 89.2% and the criteria "Very Good". So, it can be concluded that the domino card learning media on the One Variable Linear Equation and Inequality material is said to be very well used as a learning medium in the mathematics learning process.